Morphology of synthetic jet - Gil, Paweł (Advances in Mechanical and Materials Engineering)
Synthetic jet devices consist of an oscillating driver, a cavity, and a small opening such as a circular, square or rectangular orifice. When the driver is oscillating, it produces a series of vortex rings at the orifice. The device generates the zero net mass flux (ZNMF) because the identical fluid mass and the mass flow are sucked and flowed out across the orifice. Although there is no net mass transfer to its surroundings, the ZNMF device has the interesting property of causing a finite amount of momentum transfer to its surroundings. The experimental result of synthetic jet flow visualization is presented in this paper. Synthetic jet visualization is carried out using smoke visualization with light sheet. Five qualitatively different flow field regimes were identified, depending upon the Reynolds and Stokes number. Vortex ring generation and propagation are also presented and analyzed in this paper.